Laying the Foundations : Essential Elements for Assuring the Safety of Dams and Downstream Communities - Wishart, Marcus J.; Ueda, Satoru; Pisaniello, John D.; Tingey-Holyoak, Joanne L.; Lyon, Kimberly N.; Boj Garcia, Esteban (World Bank, Washington, DC, 2021)
Assuring the safety of dams is central to protecting downstream communities, infrastructure, and the environment. Dam safety is also important for securing water for productive purposes and sustaining economic development. With a global portfolio of more than 58,000 large dams, issues associated with the safety of dams and downstream communities are becoming increasingly important, particularly given aging infrastructure, increasing downstream populations, shifting demographics, and changes in climate and weather patterns. The foundation for effective dam safety assurance is an appropriate and well-designed regulatory framework that captures the legal, institutional, technical, and financial elements in the reality of a particular jurisdiction. Establishing and maintaining a regulatory framework that is fit for purpose is, therefore, necessary for ensuring the quality of dam design, construction, and operation and maintenance. The framework also ensures that safety measures are reflective of the risks inherent in managing these structures and the context in which they are developed. Such frameworks need to be developed as part of a holistic strategy for water management that is integrated in basin and regional planning processes. The objective of this policy note is to provide guidance to policy makers and practitioners on the essential elements for establishing regulatory regimes for assuring the safety of dams and downstream communities.